6 - Globalisation and Industrialisation in the Southern Africa Development Community (SADC): Challenges and Opportunities - Moyo, Theresa (Africa Development, 2020)
Over thirty years after most countries in the Southern African Development Community (SADC) attained political independence, the region still has a high level of commodity dependence and a low level of industrialisation. This article uses secondary data sources to explore the effect of globalisation on industrialisation in SADC. It concludes that globalisation has been instrumental in creating an international division of labour that shaped SADC as a commodity producer and exporter and an importer of manufactured goods. Because globalisation has imposed an industrialisation model on SADC that is not consistent with inclusivity, equity, broad-based participation and social transformation, it has not succeeded in reducing poverty and inequality in the region. Globalisation has perpetuated this structure through a neoliberal international financial and trading architecture whose policies have, until recently, been accepted and implemented by many states in the region. Paradoxically, globalisation offers immense opportunities that SADC can harness to accelerate production of high value-added goods for domestic consumption, intra-African trade, and international markets. Through regional trade agreements (RTAs), bilateral and multilateral arrangements, and partnerships with emerging economies, SADC can facilitate the implementation of the SADC Industrialisation Strategy and Roadmap, as well as national industrial policies and strategies.